An Overview on Human Helminthic Parasitology III. Cestodes, the Tapeworms - SALIM, MOHAMMAD; MASROOR, MOHAMMAD SHAHID; PARWEEN, SHAGUFTA; Singh, Amrita (European Journal of Applied Sciences, 2021)
Helminths developed a variety of diseases in humans. They are invertebrate animals usually found in the intestines of the hosts. Cestodes in association with normal ailments and diseases caused by them, they infrequently produce some other specific diseases like cysticercosis, neurocysticercosis and hydatid diseases in humans. The present review is third in the series of helminthic parasitology discussing some of the Cestodes in the light of recent researches done so far in the same field.